Analysis of the Effect of Electronic Customer Relationship Management and Customer Engagement on Customer Loyalty on Gojek Online Transportation Services Users - Alexi Yohans, Jordy; Agus Rahayu; Puspo Dewi Dirgantari (Dinasti Publisher, 2023)
Loyalty is recognized as a key indicator that can show a company's success in a competitive market competition. Activities related to customer and company contacts can maximize the realization of customer loyalty, activities referred to as customer relationship management in which in technological developments there is the concept of e-CRM. The emergence of various online transportation platforms is a phenomenon that we have encountered over the past decade. This intense industry competition makes Gojek need to plan various strategies to be able to maintain its existence. This study intends to analyze the influence of customer relationships and involvement on customer loyalty among Gojek users. The results of hypothesis testing show that there is a direct significant effect of e-CRM on customer loyalty, e-CRM on customer engagement, customer engagement on customer loyalty, and indirectly there is a significant influence of e-CRM on customer loyalty through customer engagement.